Behavioral Neurobiology of Chronic Pain - Taylor, Bradley K.; Finn, David P. (Current Topics in Behavioral Neurosciences,, 2014)
This volume brings together a series of authoritative chapters written by leading experts in preclinical and clinical aspects of pain neurobiology. It is essential reading for scientists, clinicians and students in need of a comprehensive review of behavioral readouts for the preclinical assessment of chronic pain and analgesic drug efficacy, or those with a general interest in behavioral neuroscience. At the core of this volume are emerging details of the physiology, pharmacology, and psychology of previously neglected types of chronic pain. These types include chronic post-operative pain in humans as well as animal behavioral assays that model the chronic pain of multiple sclerosis, post-herpetic neuralgia, painful diabetic neuropathy, visceral pain, latent central sensitization, and chronic muscle pain. Also emphasized are the complex bidirectional comorbidities between chronic pain and drug dependence, cognitive deficit, stress, anxiety, depression, social interaction, and prior injury history. The novel and exciting ideas introduced within this book, such as endogenous opioid dependence after tissue injury, generate real hope that effective treatment strategies for chronic pain will emerge in the near future. .